Sistemas de iluminación para túneles - Masache Neira, José Alejandro (2024)
The present research allows to understand the photometric parameters that must be met for the proper design of tunnel lighting systems, as well as the appropriate procedure to follow, in order to comply with the parameters defined in international regulations and ensure people’s safety who use these means to move from one place to another. Through an analytical methodology of different calculation methods to determine the required luminance levels in each of the sections that compose a tunnel, a calculation guide was developed that provides designers with the necessary tools to correctly and efficiently design these systems. To carry out the photometric simulations, specialized software tools were utilized to evaluate the light distribution of the selected luminaires and their positioning within the tunnel, as well as to analyze the proposed design. To validate the proposed guide, the procedure was applied to a real case, specifically to the "Túnel de los Ahorcados" located in the city of Loja. Photometric simulations were conducted using the DIALux software, and luminaires from the manufacturer Schréder were chosen, meeting the constructive requirements for this type of environment. The results obtained from the simulations were compared with the photometric parameters set by the CIE 88:2004 standard, concluding that the results obtained from the guide are greater or equal to than the requirements established in the standard. Key words: Photometric parameters, photometric simulations, tunnel sections.